Global invasion history with climate-related allele frequency shifts in the invasive Mediterranean fruit fly (Diptera, Tephritidae: Ceratitis capitata) - Pablo Deschepper; Sam Vanbergen; Massimiliano Virgilio; Andrea Sciarretta; Marco Colacci; Vasilis G. Rodovitis; Josep A. Jaques; Mario Bjeliš; Kostas Bourtzis; Nikos T. Papadopoulos; Marc De Meyer (Scientific Reports)
Abstract The Mediterranean fruit fly (Ceratitis capitata) is a globally invasive species and an economically significant pest of fruit crops. Understanding the evolutionary history and local climatic adaptation of this species is crucial for developing effective pest management strategies. We conducted a comprehensive investigation using whole genome sequencing to explore (i) the invasion history of C. capitata with an emphasis on historical admixture and (ii) local climatic adaptation across African, European, Central, and South American populations of C. capitata. Our results suggest a stepwise colonization of C. capitata in Europe and Latin America in which Mediterranean and Central American populations share an ancestral lineage. Conversely, South American invasion history is more complex, and our results partly suggest an old secondary invasion into South America from Europe or a colonization of South America directly from Africa, followed by admixture with an European lineage. Throughout its invasive range, C. capitata is challenged with diverse climatic regimes. A genome wide association study identified a relationship between allele frequency changes and specific bioclimatic variables. Notably, we observed a significant allele frequency shift related to adaptation to cold stress (BIO6), highlighting the species’ ability to rapidly adapt to seasonal variations in colder climates.